Applying habitat and population‐density models to land‐cover time series to inform IUCN Red List assessments. Issue 5 (25th February 2019) - Santini, Luca; Butchart, Stuart H. M.; Rondinini, Carlo; Benítez‐López, Ana; Hilbers, Jelle P.; Schipper, Aafke M.; Cengic, Mirza; Tobias, Joseph A.; Huijbregts, Mark A. J.
Abstract: The IUCN (International Union for Conservation of Nature) Red List categories and criteria are the most widely used framework for assessing the relative extinction risk of species. The criteria are based on quantitative thresholds relating to the size, trends, and structure of species' distributions and populations. However, data on these parameters are sparse and uncertain for many species and unavailable for others, potentially leading to their misclassification or classification as data deficient. We devised an approach that combines data on land‐cover change, species‐specific habitat preferences, population abundance, and dispersal distance to estimate key parameters (extent of occurrence, maximum area of occupancy, population size and trend, and degree of fragmentation) and hence predict IUCN Red List categories for species. We applied our approach to nonpelagic birds and terrestrial mammals globally (∼15, 000 species). The predicted categories were fairly consistent with published IUCN Red List assessments, but more optimistic overall. We predicted 4.2% of species (467 birds and 143 mammals) to be more threatened than currently assessed and 20.2% of data deficient species (10 birds and 114 mammals) to be at risk of extinction. Incorporating the habitat fragmentation subcriterion reduced these predictions 1.5–2.3% and 6.4–14.9% (depending on the quantitative definition of fragmentation) for threatened and data deficient species, respectively, highlighting the need for improved guidance for IUCN Red List assessors on the application of this aspect of the IUCN Red List criteria. Our approach complements traditional methods of estimating parameters for IUCN Red List assessments. Furthermore, it readily provides an early‐warning system to identify species potentially warranting changes in their extinction‐risk category based on periodic updates of land‐cover information. Given our method relies on optimistic assumptions about species distribution and abundance, all species predicted to be more at risk than currently evaluated should be prioritized for reassessment. Abstract : Article impact statement : Automatic screening to prioritize species reassessments optimizes the use of resources and keeps the IUCN Red List up to date. Abstract : Aplicación de Modelos de Hábitat y de Densidad Poblacional a Series de Tiempo de la Cobertura del Suelo para Informar las Valoraciones de la Lista Roja de la UICN Resumen: Las categorías y los criterios de la Lista Roja de la UICN (Unión Internacional para la Conservación de la Naturaleza) son el marco de referencia utilizado con mayor frecuencia para valorar el riesgo de extinción relativo de las especies. Los criterios se basan en umbrales cuantitativos relacionados con el tamaño, las tendencias y la estructura de la distribución y las poblaciones de las especies. Sin embargo, los datos sobre estos parámetros son escasos e inciertos para muchas especies y para otras no se encuentran disponibles, lo puede resultar en una clasificación errónea o en que se las clasifique como una especie con deficiencia de datos. Hemos diseñado una estrategia que combina datos sobre el cambio en la cobertura del suelo, las preferencias de hábitat específicas por especie, la abundancia poblacional, y la distancia de dispersión para estimar los parámetros más importantes (extensión de la presencia, área máxima de ocupación, tamaño poblacional, y grado y tendencia de la fragmentación) y así predecir las categorías de la Lista Roja de la UICN para cada especie. Hemos aplicado nuestra estrategia a las aves no pelágicas y a los mamíferos terrestres de todo el mundo (∼15, 000 especies). Las categorías pronosticadas fueron bastante consecuentes con las valoraciones publicadas por la Lista Roja de la UICN, aunque en general fueron más optimistas. Pronosticamos que el 4.2% de las especies (467 aves y 143 mamíferos) se encuentran más amenazadas que su valoración actual y el 20.2% de las especies con deficiencia de datos (10 aves y 114 mamíferos) se encuentran en riesgo de extinción. La incorporación del sub‐criterio de fragmentación del hábitat redujo estas predicciones en un 1.5 – 2.3% y 6.4 – 14.9% (dependiendo de la definición cuantitativa de la fragmentación) para las especies amenazadas y las que tienen deficiencia de datos, respectivamente, lo que resalta la necesidad de mejorar la aplicación de este sub‐criterio por parte de los asesores de la Lista Roja de la UICN. Nuestra estrategia complementa los métodos tradicionales de estimación de parámetros para las valoraciones de la Lista Roja. Además, proporciona un sistema inmediato de alerta temprana basado en actualizaciones periódicas de la información sobre la cobertura del suelo que permite identificar a las especies que, potencialmente, merezcan un cambio en su categoría de riesgo de extinción. Nuestro método está basado en suposiciones optimistas sobre la distribución y la abundancia de las especies, por lo tanto todas las especies que predecimos que tienen una mayor categoría de riesgo que la que reconoce la evaluación actual deberían ser priorizadas para su revaloración. 摘要: 世界自然保护联盟 (International Union for Conservation of Nature, IUCN) 红色名录濒危等级和评估标准是物种相对灭绝风险评估中应用得最为广泛的一套框架。这些标准的制定依据与物种分布和种群的大小、趋势和结构有关的定量阈值。然而, 许多物种这些参数的数据稀缺、具有不确定性, 甚至一些物种的数据难以获得和利用, 这可能导致它们被错误地划分濒危等级, 或被归类为"数据缺乏"。我们设计了一种方法, 结合土地覆盖变化、物种特异的生境偏好、种群丰度和扩散距离的数据, 来估计物种的关键参数 (出现范围、最大占有面积、种群大小和趋势、破碎化程度), 从而预测它们的 IUCN 红色名录濒危等级。我们应用这个方法预测了全球非远洋鸟类和陆地哺乳动物 (约 15, 000 种) 的濒危等级。预测的濒危等级与 IUCN 红色名录评估结果基本一致, 但总体上更为乐观。预测结果中, 4.2% 的物种 (467 种鸟类和 143 种哺乳动物) 比目前的评估情况更濒危, 且数据缺乏的物种中 20.2% (10 种鸟类和 114 种哺乳动物) 面临灭绝风险。进一步整合生境破碎化的子标准后, 受胁迫物种及数据缺乏物种分别减少了 1.5‐2.3% 和 6.4‐14.9% (取决于对破碎化的定量标准), 这强调了需要更好地指导 IUCN 红色名录评估者对评估标准中相关指标的应用。我们的方法是对红色名录评估中传统的参数估计方法的补充。此外, 它还提供了一个早期预警系统, 可以基于定期更新的土地覆盖数据, 来确定濒危等级可能发生变化的物种。鉴于这一方法依赖于对物种分布和丰度的乐观假设, 所有在预测中比目前评估的濒危风险更大的物种都应该优先进行重新评估。 【翻译: 胡怡思; 审校: 聂永刚】